2012
DOI: 10.1589/jpts.24.1233
|View full text |Cite
|
Sign up to set email alerts
|

The Osteoporotic Effect of Maras Powder (Turkish Smokeless Tobacco) Consumption in Healthy Males

Abstract: Abstract. [Purpose] This study analyzed the effect of Maraş powder on bone mineral density. [Subjects and Methods] One hundred and eighty-three healthy male subjects (93 Maras powder users, 90 nonusers) were included in the study. The information on demographics, health history, alcohol and tobacco use and medication use were obtained by an interviewer-administered questionnaire. Subjects who had any pathology that might affect bone mineral density, were excluded from the study. Mesurements of bone mineral de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Some studies have shown that snuff use status and periodontal bone loss are related [30], but these findings concerning the oral cavity in adults are not necessarily comparable to skeletal health, nor valid in an adolescent population. There are some studies showing that smokeless tobacco (chewing tobacco, non-combustible tobacco) accelerates age-related loss of aBMD in various populations, typically in India [31], Turkey [32], and in older multi-ethnic women [33,34]. However, it has been argued that Swedish snuff has a lower potential of harm due to reduced levels of chemical agents than tobacco products consumed by populations in other geographical areas worldwide [35] and, thus, may not be comparable with these other types of substances related to bone.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that snuff use status and periodontal bone loss are related [30], but these findings concerning the oral cavity in adults are not necessarily comparable to skeletal health, nor valid in an adolescent population. There are some studies showing that smokeless tobacco (chewing tobacco, non-combustible tobacco) accelerates age-related loss of aBMD in various populations, typically in India [31], Turkey [32], and in older multi-ethnic women [33,34]. However, it has been argued that Swedish snuff has a lower potential of harm due to reduced levels of chemical agents than tobacco products consumed by populations in other geographical areas worldwide [35] and, thus, may not be comparable with these other types of substances related to bone.…”
Section: Discussionmentioning
confidence: 99%